Determination of Manganese, Iron, Zinc, Copper and Nickel in Tilapia and Cyprinus carpio Fish Consumed in Syria by Flame Atomic Absorption Spectrometry - Antakli1, Saad; Sarkees2, Nazeera; Esraa Baghdadi1, Mahmoud (Asian Journal of Chemistry, 2014)
The present work describes a microwave digestion procedure by using new convenient digestion mixture (nitric acid and hydrogen peroxide) to determine manganese, zinc, copper, iron and nickel in (Tilapia and Cyprinus carpio) fish samples, breeding in artificial lakes, employing flame atomic absorption spectrometry. The optimization conditions involving the factors: amount of fish, microwave power and power time were studied. The experiments of this factorial were carried out using two species of local fish which are common consumed in Syria. The proposed method was used to determine the precedent metals in muscle, skin and tail in the two species fish (Tilapia and Cyprinus carpio). The relative standard deviations of the method were found to be less than 5 % for the five studied elements. The concentration results for manganese, iron, zinc, copper and nickel in Cyprinus carpio fish species varied between 1.37-3.09, 41.61-52.77, 53.44-200.71, 2.53-5.83 and 0.90-1.11 (μg/g) in muscle, 1.63-4.03, 54.81-62.45, 99.22-177.31, 2.84-7.43 and 0.74-1.15 (μg/g) in skin and 8.65-51.69, 8.48-20.60, 282.98-309.41, 0.89-1.67 and 0.77-0.96 (μg/g) in tail respectively. The variation of precedent metals in tilapia fish species varied between 0.86-2.34, 68.48-125.74, 103.36-152.68, 3.25-5.31 and 1.08-2.51 (μg/g) in muscle, 5.20-9.90, 73.12-183.62, 200.39-241.70, 2.13-5.69 and 1.09-1.90 (μg/g) in skin and 12.75-28.77, 75.39-119.75, 215.03-289.13, 1.65-3.42 and 0.99-2.45 (μg/g) in tail, respectively.